1997
DOI: 10.1159/000134534
|View full text |Cite
|
Sign up to set email alerts
|

Robertsonian chromosomal rearrangements in the short-tailed shrew, <i>Blarina carolinensi</i><i>s</i>, in western Tennessee

Abstract: We report significant heterozygosity for numerous Robertsonian translocations in the southern short-tailed shrew (Blarina carolinensis) in western Tennessee. Eight Robertsonian rearrangements were documented using G-banding techniques that explain the variability in diploid numbers from 46 throughout most of the range of the species to 34–40 in western Tennessee. These fusions resulted in the loss of telomere sequences and were not associated with nucleolar organizer regions. When heterozygocity is considered,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 21 publications
(29 reference statements)
2
24
0
Order By: Relevance
“…This study, and that of Metcalfe et al (1997), has confirmed that telomeric sequences are consistently retained during centric fusion events in taxa of the lateralis/penicillata group, in contrast to similar fusions in mice (Garagna et al, 1995;Nanda et al, 1995) and shrews (Qumsiyeh et al, 1997). It therefore appears that different fusion mechanisms consistently operate within different groups of organisms.…”
Section: Discussionsupporting
confidence: 65%
“…This study, and that of Metcalfe et al (1997), has confirmed that telomeric sequences are consistently retained during centric fusion events in taxa of the lateralis/penicillata group, in contrast to similar fusions in mice (Garagna et al, 1995;Nanda et al, 1995) and shrews (Qumsiyeh et al, 1997). It therefore appears that different fusion mechanisms consistently operate within different groups of organisms.…”
Section: Discussionsupporting
confidence: 65%
“…They were also found to be lost at the centromere regions of Rb metacentrics in some polymorphic species, in which rearrangements have occurred recently, for example, in the house mouse (Garagna et al, 1995;Nanda et al, 1995) and short-tailed shrew (Qumsiyeh et al, 1997). Also Meyne et al (1995) did not detected interstitial sites of either vertebrate or putative insect telomeric sequences in the chromosomes of several species of ants from the genus Myrmecia.…”
Section: Resultsmentioning
confidence: 94%
“…So far only a few species polymorphic for Rb fusions have been studied: Okapia johnstoni (Vermeesch et al, 1996), Akodon cursor (Fagundes et al, 1997); Blarina carolinensis (Qumsiyeh et al, 1997) and Mus musculus (Garagna et al, 1995;Nanda et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…A reduction in fertility is also seen in populations of wild mice carrying ROBs in Europe and North Africa (Capanna, 1982;Hauffe and Searle, 1993;Said et al, 1993). By contrast, shrews (Sorex araneus complex in Europe and Blarina carolinensis in Western Tennessee) show little reduction in fertility with simple ROBs (Garagna et al, 1989;Qumsiyeh et al, 1997;Searle, 1986b;Searle, 1990). While variations in Sorex have evolved to fixation of chromosomal races, data on Blarina suggest an earlier stage of this evolutionary process (Qumsiyeh et al, 1997, and data presented here).…”
mentioning
confidence: 52%